Layanan informasi karir dan pemahaman lanjutan studi siswa SMA - Ulfa Mahera; M. Husen; Nurbaity Bustamam (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2021)
Career information service is a form of career guidance service that can help students prepare for one’s career development. This study is intended to describe students' experiences of career information services, describe the condition of students' understanding of further studies, and use this data to estimate the determination index of providing career information services on students' understanding of further studies. The study used a quantitative approach with descriptive and correlational research designs. The research was conducted at one of the schools in Aceh Besar District. Based on 400 total population, a sample of 121 students was taken using a simple random sampling method. Data were collected using the student experience scale of career information services and the understanding of advanced studies scale. The answer options used for the scale adopt the Likert Scale answer options. The results showed that the dominant student's career information service experience was in the high category (57%), students' understanding of the dominant career information service was in the high category (48.8%). The calculation of the index of determination of these two variables shows that 25.3% of the variation in students' understanding of advanced studies can be explained by the provision of career information services in schools. Keywords: Career information services; understanding of further studies; high school level students; correlational studies ABSTRAK Layanan informasi karir merupakan salah satu bentuk layanan bimbingan karir yang dapat membantu siswa mempersiapkan diri sehubungan dengan perkembangan karir. Penelitian ini ditujukan untuk menggambarkan pengalaman siswa terhadap layanan infomasi karir yang telah dilaksanakan, menggambarkan kondisi pemahaman siswa mengenai lanjutan studi, serta menggunakan data ini untuk memperkirakan indeks determinasi dari pemberian layanan informasi karir terhadap pemahaman lanjutan studi siswa. Penelitian menggunakan pendekatan kuatitatif dengan desain penelitian deskriptif dan korelasional. Penelitian dilakukan pada salah satu sekolah di Kabupaten Aceh Besar. Berdasarkan 400 jumlah populasi diambil sampel sebanyak 121 siswa dengan metode penarikan sampel acak sederhana. Data dikumpulkan menggunakan skala pengalaman siswa mengenai layanan informasi karir dan skala pemahaman lanjutan studi. Opsi jawaban yang digunakan untuk skala mengadopsi opsi jawaban Skala Likert. Hasil penelitian menunjukkan bahwa pengalaman layananan informasi karir siswa dominan berada pada kategori tinggi (57%), demikian juga pemahaman siswa terhadap layanan informasi karir dominan berada pada kategori tinggi (48,8%). Perhitungan indeks determinasi dari kedua variabel ini menunjukkan bahwa 25,3% variasi pada pemahaman lanjutan studi siswa dapat dijelaskan oleh pemberian layanan informasi karir di sekolah.